Perancangan UI/UX Aplikasi Booking Online Pada Elaine Studio Dengan Metode Design Thinking - Kasih, Andaristy Mutiara; Ismail, Ismail (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Nail art is currently experiencing a significant increase in popularity, driven by beauty trends and growing consumer preferences. The nail art salon industry is undergoing growth and transformation driven by new trends and technological advancements. This makes it an exciting time for salon owners looking for solutions by adopting technology to help businesses attract more customers and also increase customer satisfaction. The process of booking appointments and providing information on Elaine Studio is still done manually, namely booking through social media such as Instagram, Whatsapp or directly face to face to come to the studio and is also still recorded manually to book an appointment. This study aims to design and develop an effective user interface (UI) and User Experience (UX) for the nail art online booking mobile application using the Design Thinking method. The main focus of the study is to create an intuitive and user-friendly design, which is able to increase ease of Use and user satisfaction. After going through a series of design and testing iterations, the application is tested using the system Usability Scale (SUS) method to evaluate its usability level.